Micromechanical Properties and Collagen Composition of Ruptured Human Achilles Tendon. (February 2013) - Hansen, Philip; Kovanen, Vuokko; Hölmich, Per; Krogsgaard, Michael; Hansson, Patrick; Dahl, Morten; Hald, Martin; Aagaard, Per; Kjaer, Michael; Magnusson, S. Peter
Background: The Achilles tendon is one of the strongest tendons in the human body, and yet it frequently ruptures, which is a substantial clinical problem. However, the cause of ruptures remains elusive. Hypothesis: Ruptured human Achilles tendon displays inferior biomechanical properties and altered collagen composition compared with noninjured tendon. Study Design: Controlled laboratory study. Methods: Biopsy specimens were obtained at the rupture site and the noninjured part of the tendon (internal controls) in 17 patients with acute Achilles tendon rupture. Age- and weight-matched human cadaveric Achilles tendons (external controls) were also obtained. Tendon samples were tested micromechanically and biochemically. Results: The mean Young modulus was lower ( P < .01) in ruptured (256.7 ± 100.8 MPa) and internal control tendon (262.4 ± 111.5 MPa) compared with external control tendon (512.9 ± 209.6 MPa; P < .01), whereas failure strength did not display similar differences ( P = .06-.16). Collagen content, lysyl pyridinoline (LP), hydroxylysyl pyridinoline (HP), and pentosidine (PENT) did not display regional differences between ruptured and noninjured tendon. However, collagen content was less in ruptured (0.457 ± 0.093 mg/mg) and noninjured tendon (0.476 ± 0.072 mg/mg) compared with external control tendon (0.585 ± 0.044 mg/mg, P < .001). Pentosidine was similar in all tendon samples and was positively related to age in all samples ( r 2 = 0.44-0.72, P < .05). Collagen content was positively related to failure stress but only in ruptured samples ( r 2 = 0.36; P < .05). HP, LP, and PENT content were unrelated to failure stress and Young modulus in ruptured, noninjured, and cadaveric tendon. Conclusion: These data imply that there may be a mechanical weakening of the tendon and that a reduced collagen content may be related to the pathophysiological characteristics of Achilles tendon rupture. Clinical Relevance: Earlier studies have demonstrated that specific training regimens to treat tendon injury can improve tendon composition and mechanical properties. This study supports the notion that treatment measures should aim to increase tendon collagen content and improve micromechanical quality of the tendon matrix.